Hematoma block for fracture reduction - Bajracharya, Suraj; Bajracharya, Tamanna; Shrestha, Shriraj (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Distal radius fractures are one of the commonest fractures and more commonly involve children and elderly. Analgesia during reduction are determined by safety, simplicity, effectiveness and costs. The objective of this study is to evaluate the effectiveness of the Hematoma Block (HB) for reduction in distal forearm fractures in a developing country like Nepal. Methods: The study design was double blind randomized control trial performed at tertiary care hospital from July 2016 to August 2017. The patients having radiologically confirmed distal forearm fractures less than 96 hours old in 46 males and 54 females included after obtaining informed consent. 50 patients receiving Brachial Plexus Block (BPB group), and 50 patients receiving HB group during reduction of distal forearm fractures were initially allotted in two arms of randomized group. Pain measured by Visual Analogue Scale (VAS) was recorded before, during, and after reduction. Results: The study showed that HB with (mean ± SD) a VAS score of 2.08 ± 0.85 was as effective as BPB with a VAS of 1.7 ± 0.64 in terms of producing analgesia ( p=0.013), with the advantage of no motor paralysis and a significantly higher reduction rate, odds 3.45, 95% CI 1.52 – 7.85, p = 0.0013. 1/50 patients in brachial plexus block had bronchospasm needing intubation and ICU care where as 1/50 patient with hematoma block and infection which needed incision drainage and external fixation for complete healing. Conclusions: “The Hematoma Block” is to be encouraged in our set up for the reduction of the distal forearm fractures. The technique may be used in those fractures like isolated ulna fractures, minially displaced tibial fractures, fracture fibula where local anesthesia can be easily infiltrated percutaneously The study may be beneficial in managing such fractures and hence, it will help change in therapeutic policies comparing other modalities.